Singapore accounting education : towards the 21st century - Lim, Cheng Chye (2014)
Accounting has always been an integral part of an ever-changing business world. As such, accounting education is dynamic and requires constant review to match social expectation. The purpose of this report is to trace the development of Singapore accounting education into its present form and to identify the changes that are likely as we approach the twenty-first century. Research has been focused on the history of the current School of Accountancy and Business and literature by various academics on the accountancy education system. In the light of current emphasis on regionalisation and globalisation, a survey on past accountancy graduates was carried out, together with comments from NTU lecturers, which provide feedback for improving the present curriculum. It is hoped that this report will be useful in the planning of accounting education for the next century.